The Impact of Operating Cash Flow on Corporate Profitability: Amman Stock Exchange case study - Kamal Ahmad , Kadhm; Hasan Salih, Kaiwan; Saeed Sangawi, Shakhawan (Journal of Economics and Administrative Sciences, 2024)
The problem of the study is the challenges faced by the growth of different sectors, which requires the identification of an appropriate operating cash flow policy to increase corporate Profitability. Unbalanced policies followed in operating cash flows can negatively affect companies' Profitability.The study's objective is to investigate the impact of operating cash flow on the Profitability of companies in different sectors listed on the Oman Stock Exchange. For five years (2017–2021) for 71 companies. In these sectors, Profitability and metrics have been used carefully. To show how these elements affect the success of each of these sectors? It is because investors can use this information to make sound investment decisions using different operating cash flow methods to evaluate company profitability. The researchers created a checklist to test the research hypothesis, in which each operating cash flow (OCF) was used as an independent variable. (Return on Assets (ROA) and Return on Equity (ROE)) was determined as the type of firm Profitability, which is the dependent variable. The results are shown through two models. Data using descriptive statistical analysis. Regression Approaches Using EViews 12, Given that the data included both time series and cross-sectional characteristics, fixed least squares (PLS) regression effects models were used to estimate the study models.The results reveal that operating cash flow has an impact of 57.9% on ROA, a measure of corporate Profitability, and other variables have an impact of 42.1% that is not mentioned. Meanwhile, the independent variable affects ROE by 57.7% and other variables by 42.3%. Paper type: Research paper.